Parenting Styles and Social Phobia in Iraqi Teens: Gaya Pengasuhan Anak dan Fobia Sosial pada Remaja Irak - Anwar asmail; Kareem Sajit (Academia Open, 2024)
This study evaluated the socio-demographic characteristics and social phobia levels of 385 secondary school students in the Thi-Qar Governorate of Iraq. Using a descriptive, cross-sectional design, data were collected via questionnaires and analyzed with IBM SPSS 20.0. Results indicated that students, predominantly from nuclear families and moderate-income homes, exhibited mild to moderate social phobia (M±SD = 32.47±7.852). Permissive parenting styles were linked to higher social phobia, with notable differences between mothers' and fathers' influences. The study underscores the need for school-based psychological support programs and calls for further research with larger, more diverse samples. Highlight: Students exhibited mild to moderate social phobia (M±SD = 32.47±7.852). Permissive parenting styles linked to higher social phobia. Recommends school-based psychological support programs. Keyword: socio-demographic, social phobia, secondary students, parenting styles, Iraq